Editorial to the Special Issue - Angel Asensio; Dany Lang (Intervention. European Journal of Economics and Economic Policies, 2011)
The last few years have been characterized by a significant renewal and development of post-Keynesian modelling (PKM hereafter). For obvious reasons, this growing interest has been reinforced since the 2007 crisis, a tragic event that has confirmed the relevance of PKM. The papers gathered in this issue are amongst the most stimulating ones that were presented at a conference dedicated to this issue, organised by the Center of Economics of Paris North (CEPN), University of Paris 13, on November 20–21, 2009.
Keywords: 330